THE EFFECT OF EDUCATION AND HEALTH CARE EXPENDITURE ON GDP IN EU COUNTRIES - GORDIENKO, Ludmila; PASICHNYK, Yurii; SMAKOVSKAYA, Yuliya (Journal of European Economy, 2021)
The paper analyses the peculiarities of public expenditure on education and health care in eight EU countries grouped by population. Trends in the outcomes are revealed. Applying correlation and regression analysis to Eurostat data, the significance of influence of these expenditure on GDP during 2011-2019 is determined. It is established that health care expenditure have a positive effect in all countries, while education expenditure have not had a significant impact on economic development in some countries. These expenditure are proven to have a varying influence on GDP depending on budget capacity of any given country, government priorities, effectiveness of use and support for dynamic financing. JEL: I18, I28, 011.